Financial accounting : volume 2 - Valix, Conrado T.; Peralta, Jose F.;Valix, Christian Aris M. (Recto, Manila : GIC Enterprises & Co. Inc., 2015)
This book is designed to cover the financial accounting standards relative to the recognition, measurement, statement presentation and disclosure requirements of liabilities and shareholders equity.
1. Liabilities -- 2. Premium and warranty liability -- 3. Accrued liabilities and deferred revenue -- 4. Provision and contingent liability -- 5. Bonds payable -- 6. Effective interest method -- 7. Compound financial instrument -- 8. Note payable -- 9. Debt restructure -- 10. Operating lease -- 11. Financial Lease -- Lessee -- 12. Direct financing Lease--Lessor -- 13. Sales type lease--Lessor -- 14. Sale and leaseback -- 15. Accounting for income tax -- 16. Postemployment benefits -- 17. Other employee benefits -- 18. Shareholders equity --19. Retained earnings -- 20. Share-based compensation -- 21. Share appreciation right -- 22. Book value per share -- 23. basic earnings per share -- 24. Diluted earnings per share -- 25. Multiple choice problems.
Keywords: MANAGERIAL ACCOUNTING